Hidroponik Organik Berbasis Pupuk Organik Cair - NI NENGAH SONIARI; NI WAYAN SRI SUTARI (Fakultas Pertanian Universitas Udayana, 2023)
Organic hydroponics based on liquid organic fertilizer. Research on the cultivation of Kailan (Brassica oleracea var. achepala) plants using an organic hydroponic system based on organic fertilizers (POC), was conducted at the experimental garden of Pasraman Unud Jimbaran from March to June 2020. The liquid organic fertilizer used consisted of two types of MOL, namely bamboo shoots MOL and banana weevil MOL. The purpose of this research is to find an organic medium (nutrient solution) that is cheap, easy and environmentally friendly as an alternative substitute. AB mix (inorganic nutrients) which has been used in hydroponic systems. The experimental design used in this study was a Randomized Block Design. Using liquid organic fertilizer from MOL Bamboo Shoots (R) and MOL Banana Hump (B). The treatments consisted of: K (without MOL); K+ (without MOL +AB mix) ; R1& B1 ( 50 ml/L ); R2 & B2 (100 ml/L) ; R3 & B3 (150 ml/L); and R4 & B4 (200 ml/L), there were 10 treatments with 3 replications, so there were 30 experimental units. Initial analysis of the media was carried out on the levels of N, P, K, pH and EC. Parameters measured were number of leaves, plant height, wet weight, plant dry weight. The results showed that hydroponics by only relying on liquid organic fertilizer as a source of nutrition, was not able to support normal plant growth. Wet weight, dry weight and plant height of Kailan in the MOL treatment of banana weevil and MOL of bamboo shoots showed much smaller results, namely 1/10 compared to the AB mix (K+) treatment.